Analysis of Ease of Use and Transaction Security in Interest in Using Brimo and User Trust as Mediation (Survey on BRIMO Sukabumi users) - Gunawan, Handi; Rachmawati, Ike; Sunarya, Erry (Universitas Muhammadiyah Pontianak, 2025)
This study aims to determine the effect of ease of use and transaction security on interest in using BRImo, as well as the role of user trust as a mediating variable for BRI customers in Sukabumi. A quantitative approach was used in this study with a survey method of 399 active BRImo user respondents. Data analysis was conducted using Partial Least Square with the help of SmartPLS 4.0 software. The results showed that both ease of use and transaction security had a positive and significant effect on interest in using BRImo. In addition, user trust is proven to be able to mediate the relationship between ease of use and transaction security on interest in using. The highest mean on the interest in using variable is found in the indicator of recommendation to use BRImo, while the lowest mean is found in attraction due to ease of transactions. Overall, respondents' perceptions of all variables are high, but there is still room for improvement, especially in the aspects of overall experience, transaction security, and technical service capabilities. These findings indicate the importance of comprehensively improving the quality of user experience to encourage loyalty and intensity of use of BRImo in the future.